Produktivitas Rumput Laut Kappaphycus alvarezii pada Musim yang Berbeda di Perairan Rote Ndao, Nusa Tenggara Timur - Wildan Faturrachman Emaona; Ade Yulita H. Lukas; Jusuf Roniena Manilapai (Jurnal Aquatik, 2026)
Seaweed, particularly Kappaphycus alvarezii, is a leading commodity with high economic value due to its carrageenan content, which is widely used in the food, cosmetics, and pharmaceutical industries. Seaweed cultivation productivity is strongly influenced by aquatic environmental conditions, including seasonal dynamics. This study aims to analyze the effect of seasonal variations (rainy season, transition season, and dry season) on seaweed productivity in Rote Ndao Regency. The study was conducted from June to August in Daiama Village, Landu Leko District, using a survey method through interviews With seaweed farmers using questionnaires. Data were analyzed using pearson correlation and One-Way ANOVA. The results showed that the highest productivity occurred in the transition season, followed by the dry season, and the lowest in the rainy season. The Pearson Correlation test showed a significant relationship between season and productivity with a correlation coefficient value of 0.422 (p < 0.05), indicating a moderate relationship with a positive direction. Ecologically, the transition season provides more stable and optimal water conditions for seaweed growth, while the rainy and dry seasons tend to put environmental pressure. Thus, the season significantly impacts seaweed productivity, making determining the right planting time a crucial factor in optimally and sustainably increasing cultivation yields. Key words: Kappaphycus alvarezii, produktivity, rote ndao, season, seaweed